La Constitución y la desobediencia civil como proceso en la defensa de los derechos fundamentales - Aguilera Portales, Rafael Enrique (2023)
Actually, social movements are turning on the new social subject, who injects new ethical and political impulses to the society. The ideas of Ronald Dworkin supposes a conception of the constitution interpretation and application without the monopoly by the State instances, but understood like a task within the citizens ́ interpretations. An integrative and non authoritarian conception about the judicial control of law constitutional control is opposed to an absolute and exclusive view of jurisdictional organs, enlarging the concept of jurisdictional democracy.